Primary plasma cell leukaemia in a 22-year-old woman: A case report - Robyn Marshall; Jenifer Vaughan; Ria David; Elise Schapkaitz; Sergio Carmona; Tracey Wiggill (AOSIS, 2015)
Introduction: Primary plasma cell leukaemia is a rare and highly aggressive disease that is commonly diagnosed a decade earlier than multiple myeloma, at a median age of 55 years. However, it has also been described in younger patients, as documented in this case report. It often presents with hepatosplenomegaly and lymphadenopathy, whilst the presence of bony lesions are less-commonly seen when compared to multiple myeloma. Case presentation: This report describes the case of a young woman who presented with symptoms of anaemia and a history of menorrhagia. On further careful examination, she was found to have additional signs and symptoms and was later diagnosed with primary plasma cell leukaemia. Management and outcome: On admission, the patient received supportive care measures, including blood products. At diagnosis, a specific chemotherapy regimen was commenced; however, this failed to induce remission. The decision to continue with supportive care only was made and the patient died seven months later. Discussion: This case study is presented because of its rarity, the young age of the patient at presentation and the unusual clinical and laboratory findings. Persistent anaemia unresponsive to standard treatment should raise the index of suspicion and further investigations directed to exclude malignancies should be considered.   (Full article to follow)